Applying the Principle of Protesting theLegal Action Against the Parties to the Action: Comparative Analytical Study - نامق حسين اسماعيل; محمد صالح ريبوار (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Legal conduct has a material effect not only on the parties involved but on everyone else as well. Accordingly, the parties to legal conduct can use these legal conducts to decide how to deal with each other and with anyone else based on legal conduct. There are different types of legal conduct, such as unilateral, bilateral, and collective conduct, and each has its own meaning and implementation. Additionally, there are casual and formal conditions for implementing the principle of using legal conduct. In formal settings, such as not cheating, but in casual settings, it’s the form of behavior and writing it down based on the type of conduct. Our research followed a comparative approach, and we found that the Iraqi legislator, like the Egyptian one, did not regulate this principle; nevertheless, the French legislator did, according to the new contract law released in 2016. This means that legal conduct is a fact, and everyone should follow and obey it, regardless of whether it complies with the law. To avoid legal disputes, we suggest that parties abide by the rules arising from the legal conduct, and the parties should refer to the legal conduct in dealing with others.